1993
DOI: 10.1677/joe.0.139r001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Asn87 and Asp318 mutations on ligand binding and signal transduction in the rat GnRH receptor.

Abstract: The gonadotrophin-releasing hormone (GnRH) receptor is unlike other G-protein coupled receptors in that the highly conserved amino acids, Asp in the second transmembrane region and Asn in the seventh, are interchanged. Site-directed mutagenesis studies mutated these residues back to their normally conserved positions. Two single mutants Asn87Asp & Asp318Asn and one double mutant Asn87Asp Asp318Asn were transiently expressed in COS-1 cells and their effect on binding to GnRH and inositol phosphate production me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…A fourth residue also considered important in the hydrogen bonding is asparagine in the (N/D)PXXY motif in the seventh transmembrane domain of GPCRs (10). Contrary to our expectations, based on results from homologous substitutions on other GPCRs (12,14,24), the N297A mutation did not affect G protein coupling. This result was confirmed using another N297A clone from a separate transfection.…”
Section: The Effect Of Transmembrane and Cytoplasmic Mutations On Fprcontrasting
confidence: 99%
See 2 more Smart Citations
“…A fourth residue also considered important in the hydrogen bonding is asparagine in the (N/D)PXXY motif in the seventh transmembrane domain of GPCRs (10). Contrary to our expectations, based on results from homologous substitutions on other GPCRs (12,14,24), the N297A mutation did not affect G protein coupling. This result was confirmed using another N297A clone from a separate transfection.…”
Section: The Effect Of Transmembrane and Cytoplasmic Mutations On Fprcontrasting
confidence: 99%
“…In the wild-type gonadotropin-releasing hormone receptor, the conserved aspartic acid in TMII has been replaced with an asparagine, and the conserved asparagine in TMVII has been replaced with an aspartic acid. A N87D mutation resulted in loss of ligand binding and a D318N mutation resulted in abolished inositol phosphate production (12,13). However, a double mutant N87D/D318N re-established inositol phosphate production (12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Receptor Binding Assay-Ligand binding assays were carried out on cell membranes from receptor expressing cells as described previously (17). Briefly, purified membranes were incubated for 120 min in assay buffer (40 mM Tris⅐HCl, 2 mM MgCl 2 , 0.1% BSA, pH 7.4) at 4°C with 125 Ϫ10 to 10 Ϫ6 M. The membranes were then filtered, and the radioactivity was counted.…”
Section: Methodsmentioning
confidence: 99%
“…While the inter-related roles of these H2 and H7 side chains in receptor activation (9 -12) suggest that they constitute a structural and functional microdomain, this conclusion has been considered controversial (13,14). The initial study of this microdomain in the GnRH receptor reported that the presence of an Asp residue in both loci eliminated detectable binding.…”
mentioning
confidence: 99%